Experimental study of the morphine de-addiction properties of Delphinium denudatum Wall. - Kumar Anil; Ali Khan Rahat; Rahman Syed (BMC, 2002)
Abstract Background Our aim was to explore the de-addiction properties of Delphinium denudatum Wall. in morphine dependent rats. Methods Charles Foster male albino rats were made morphine dependent by injecting morphine sulphate in increasing doses twice a day for 7 days. The spontaneous withdrawal signs observed 12 h after the last dose were quantified by the 'counted' and 'checked' signs. The drug (alcoholic extract of Delphinium denudatum) was administered p.o. in different regimen: a) single dose (700 mg/kg) 10 h before the first dose of morphine, b) single dose (700 mg/kg) 10 h after the last dose of morphine, c) multiple doses (350 mg/kg) along with morphine twice a day for 7 days. Result Administration of Delphinium denudatum extract caused significant reduction in the frequency of counted signs as well as the presence of checked signs of morphine withdrawal. The maximum reduction was observed in regimen 'b' followed by regimen 'c' and 'a'. Conclusion Delphinium denudatum Wall. significantly reduces the aggregate scores for all parameters in morphine withdrawal syndrome by central action and thus may prove to be an alternative remedy in morphine de-addiction.